Prevention of injuries in young female players in European team handball. A prospective intervention study - Wedderkopp, N.; Kaltoft, M.; Lundgaard, B.; Rosendahl, M.; Froberg,K. (Scandinavian Journal of Medicine & Science in Sports, 1999)
Young female players in European handball have a very high injury incidence, up to 50 injuries per 1000 hours of game. More than half of these injuries happen without any external cause. The aim of the study was to investigate the effect of an intervention programme designed to reduce the number of injuries in young female players in European handball, with special emphasis on injuries in the lower extremities. The programme was created using elite athlete training programmes and those designed for rehabilitation of injured athletes with functional instability of their ankles and rupture of the anterior cruciate ligament. It included the use of an ankle disk for 10-15 min at all practice sessions, for one 10-month season (August 1995-May 1996).Twenty-two teams participated in the study, and were randomly assigned to the intervention or control group. Eleven teams with 111 players were randomised to the intervention group and 11 teams with 126 players to the control group. Data were analysed using a t-test for continuous variables, chi2-analysis and Fisher's exact test for dichotomous variables and multivariate methods to determine odds-ratios. The results indicated that using the intervention programme decreased the numbers of both traumatic and overuse injuries significantly. The differences in injuries between the groups were 80% during games and 71% during practice. In addition, the players in the control group had a 5.9 times higher risk of acquiring an injury than the players in the intervention group.